Getting near to baby - Couloumbis, Audrey (New York : Scholastic Books, 2000)
Although thirteen-year-old Willa Jo and her Aunt Patty seem to be constantly at odds, staying with her and Uncle Hob helps Willa Jo and her younger sister come to terms with the death of their family's baby.
740
Keywords: Sisters -- Fiction; Grief -- Fiction; Death -- Fiction; Aunts -- Fiction